Potential use of beet-pulp concentrate supplementation in athletic horse - Luzilene Araujo de Souza; Monica Miranda Hunka; Sigismundo Fassbender de Rezende Júnior; Carolina Jones Ferreira Lima da Silva; Helena Emília Cavalcanti da Costa Cordeiro Manso; Joana Simões; Clarisse Simões Coelho; Francesco Fazio; Francesca Aragona; Hélio Cordeiro Manso Filho (Heliyon)
The aim of this two-phase study was to evaluate the use of beet pulp concentrate (BPC) in athletic horses. On the first trial the effects of supplementation with 820g of BPC for 12 weeks were assessed and a crossover postprandial curves of blood biomarkers were determined in five adult Arabian mares. Differences were found in T-chol, HDL-chol, TPP and MCHC (p < 0.05). Postprandial curves varied among challenges (p < 0.05) for glucose, insulin, and hematocrit. These results confirmed that BPC supplementation led to changes in blood biomarkers, without inducing major metabolic disruption. The aim of the second trial was to evaluate effects of resistance training using a horse walker in eight yearling gaited foals fed with BPC (16 %) for 12 weeks. Blood samples were collected before and at 30, 60 and 90 days of training and results demonstrated the highest level of [NEFA] and [triglycerides] at end of experimental period (p < 0.05) and increased of growth hormone after exercise sections after 60 days (p < 0.05). Also, [MCHC] and [Hb] increased 30 days after beginning of training program (p < 0.05), maintaining until the end of trial period. Association of the training program with highly digestible fiber as BPC possibly led to a greater availability of NEFA and hCG certainly helping the physical conditioning of these young animals.